Monetary policy and dynamic adjustment of corporate investment: A policy transmission channel perspective - Qiang Fu; Xing Liu (China Journal of Accounting Research, 2015)
We investigate monetary policy effects on corporate investment adjustment, using a sample of China's A-share listed firms (2005-2012), under an asymmetic framework and from a monetary policy transmission channel perspective. We find that corporate investment adjustment is faster in expansionary than contractionary monetary policy periods. Monetary policy has a significant effect on adjustment speed through monetary and credit channels. An increase in the growth rate of money supply or credit accelerates adjustment. Both effects are significantly greater during tightening than expansionary periods. The monetary channel has significant asymmetry, whereas the credit channel has none. Leverage moderates the relationship between monetary policy and adjustment, with a greater effect in expansionary periods. This study enriches the corporate investment behavior literature and can help governments develop and optimize macro-control policies.
Keywords: G31; E52; 650; Monetary policy; Transmission channels; Asymmetric effect; Corporate investment; Dynamic adjustment